2016
DOI: 10.2754/avb201685030267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mannan oligosaccharide supplementation on blood and intestinal immune cells, bacteria numbers and performance in weaned pigs

Abstract: In animal production, alternative strategies to the use of antibiotic growth promoters have stimulated research of dietary supplements to increase resistance, reduce post-weaning gut disorders and growth checks in pigs. This study was performed to determine the influence of dietary mannan oligosaccharide as a potential alternative to antibiotic growth promoters in weaned pigs on: (1) proliferation of circulating and intestinal immune cell subsets, (2) incidence and severity of diarrhoea, and (3) performance du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Beyond their ability to modulate gut microbiota, MOS supplementation evidenced additional beneficial properties such as decreased incidence of diarrhoea [21,22] and higher growth performance [23,24]. Usually, the most significant results on growth when supplementing MOS in swine are obtained during the first and second week just after weaning [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond their ability to modulate gut microbiota, MOS supplementation evidenced additional beneficial properties such as decreased incidence of diarrhoea [21,22] and higher growth performance [23,24]. Usually, the most significant results on growth when supplementing MOS in swine are obtained during the first and second week just after weaning [25].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature has also evidenced the efficacy of dietary MOS to enhance pigs' immunity by the increase in the immunoglobulin serum concentrations [28], the stimulation of the mucosal immunity [21], and the modulation of the inflammatory response [29]. Duan et al [29] reported decreased serum concentration of proinflammatory cytokine and increased circulating levels of anti-inflammatory cytokine Interleukin-10 in young piglets following the administration of 0.8 mg/kg BW of MOS.…”
Section: Introductionmentioning
confidence: 99%
“…Functional oligosaccharides are widely used in animal feed because of the benefits to animal growth and immunity (Duan et al, 2016). Mannanoligosaccharide (MOS) has been identified as a typical functional oligosaccharide (Patel and Goyal, 2011) and has been the subject of several studies on animals including pigs (Giannenas et al, 2016;Valpotic et al, 2016), laying hens (Bozkurt et al, 2016;Ghasemian and Jahanian, 2016), broiler chickens (Attia et al, 2014), rabbits (Abdel-Hamid and Farahat, 2016), and aquaculture (Akter et al, 2016;Torrecillas et al, 2016). Most previous studies concentrated on monogastric animals, because it is believed that oligosaccharides are degraded by ruminal microbes and therefore bring no additional benefit to ruminant diets.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic growth promoters have been banned by the European Union in food animal production since 2006 (Valpotić et al 2016). Therefore, looking for a cost-effective method becomes a very rewarding issue, especially natural materials capable of maintaining animal health and improving growth performance is widely accepted.…”
Section: Introductionmentioning
confidence: 99%